Palmtop Computer-Assisted Group Therapy for Social Phobia. - Przeworski, Amy; Newman, Michelle G. (Journal of Clinical Psychology, 2004)
This article describes the application of group computer-assisted therapy for social phobia. The computer program includes a diary function for ongoing self-monitoring of anxiety as well as guidance on the practice of relaxation, cognitive restructuring, and self-control desensitization. Although the program was originally designed to treat individuals with generalized anxiety disorder (GAD), it was hypothesized that the program also would be effective for individuals with social phobia; therefore, it was implemented in a group of individuals with a primary diagnosis of GAD or social phobia. We present the case of a client with social phobia who received six sessions of group therapy and who carried the ambulatory computer throughout this treatment. Outcome data suggest that the treatment was highly effective for this client as well as others with a diagnosis of social phobia or GAD. Reprinted by permission of the publisher.